MAJELIS TAKLIM SEBAGAI BASIS PEMBERDAYAAN UMAT - Firman Nugraha (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
The aims of this article is to describe comparatively the model of community developmentbase on majelis taklim. The rationale framework is used that Islam and Muslims who become the majority can become social capital for community development. The results of this study conclude that the social context being the entry point for community empowering. The articulation of the developmentactivism was adjusted to the real problems. So that from the two majelis taklim are studied show a different development models, but in the same spirit to defend to the opressed.  Key words: Majelis Taklim, Transformative Councelling, the Oppressed, Islamic Economy.